(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
This project aims to develop an investigation about actions and ideas of the policemen of Anti-Fascism Movement in Brazil. This research is situated in the field of left-winger military that as a concept will suit of analytical instrument of the data and will become intelligible to cops. As a field of study, it will be related to Policing studies. From these assumptions, will be investigated 1) the instrumental analytical means too effective to carry out their actions; 2) the party political articulations in the corporations; 3) ideas of policing; and 4) the meaning of democracy to them. The qualitative and quantitative approaches integrate the methodological procedure that have as a field of investigation the digital media, with emphasis to Facebook that will serve as virtual space to obtain primary data; the online questionnaire application, through Google forms; beyond the bibliographic survey to outline the debates on democracy before the Federal Constitution of 1988 in Brazil. Keywords: Anti-Fascist Policemen. Digital media. Left-winger military. Policing Studies. Democracy.